2005
DOI: 10.1016/s1572-1000(05)00030-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms in photodynamic therapy: part two—cellular signaling, cell metabolism and modes of cell death

Abstract: Photodynamic therapy (PDT) has been known for over a hundred years, but is only now becoming widely used. Originally developed as a tumor therapy, some of its most successful applications are for non-malignant disease. In the second of a series of three reviews, we will discuss the mechanisms that operate in PDT on a cellular level. In Part I [Castano AP, Demidova TN, Hamblin MR. Mechanism in photodynamic therapy: part one-photosensitizers, photochemistry and cellular localization. Photodiagn Photodyn Ther 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
454
0
20

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(480 citation statements)
references
References 172 publications
6
454
0
20
Order By: Relevance
“…Cellular localization is an important issue, since it is related with the mechanism of cell death trigger. Photosensitizers localized within mitochondria are mostly associated with the apoptotic (some autophagic) death mechanism involved, i.e., caspase (or caspase-independent) activation and mitochondrial dysfunction (potential disruption of mitochondrial membrane and cytochrome C release) giving rise to morphological changes: bleeding, chromatin condensation and alteration of cell adhesion molecules (29)(30)(31)(32)(33)(34). Confocal images show overlapping of PpIX red fluorescence and MitoTracker Green fluorescence which strongly suggest PpIX mitochondrial localization in infected and non-infected THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular localization is an important issue, since it is related with the mechanism of cell death trigger. Photosensitizers localized within mitochondria are mostly associated with the apoptotic (some autophagic) death mechanism involved, i.e., caspase (or caspase-independent) activation and mitochondrial dysfunction (potential disruption of mitochondrial membrane and cytochrome C release) giving rise to morphological changes: bleeding, chromatin condensation and alteration of cell adhesion molecules (29)(30)(31)(32)(33)(34). Confocal images show overlapping of PpIX red fluorescence and MitoTracker Green fluorescence which strongly suggest PpIX mitochondrial localization in infected and non-infected THP-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, carcinoma induction after PDT of normal skin has not been noticed. 51 However, because of the latent period in cancer development, long-term follow up is desired 5,6 even though PDT may confer advantages over conventional treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are several processes involved in causing PDT induced cell killing it is not surprising that any of the three commonly known cell death mechanisms, namely apoptosis, necrosis or autophagy can be triggered [5,10,23,26,54]. Confocal microscopy and Förster Resonance Energy Transfer (FRET) imaging on cultured cells demonstrated that common PDT PSs are found to localize in different subcellular structures such as the plasma membrane (Photofrin®), mitochondria (phthalocyanine Pc4), lysosomes, nucleus, endoplasmic reticulum or the Golgi apparatus [5,23,26,43,55].…”
Section: Figurementioning
confidence: 99%
“…This may not only induce secondary necrosis, but also lead to the overexpression of vascular endothelial growth factor (VEGF) to make up for the loss of blood vessels. Hence the combination of PDT with antiangiogenic agents has been suggested to improve PDT treatment outcomes [5,23,26,54].…”
Section: Figurementioning
confidence: 99%